KOMUNIKASI KYAI DI PERGURUAN TINGGI - Iwan Kuswandi (Institut Dirosat Islamiyah Al-Amien Prenduan, 2018)
In pesantren, Kyai (moslem scholars) are the figure who have domain role, it is different in higher education that has formal organization where has structural, fungsional, and bureaucracy well, it doesn’t depend on one figure only. In this research focuses on communication patterns kyai for moral development at university. This study has also found that patterns of communication used by kyai in the coaching character in university is interpersonal communication patterns and communications group. Kyai in universities use one-way communication models, two-way and interactive communication models, transaction communication models, transmission communication models, expressive ritual communication models, publicity communication models, and reception communication models.